2008
DOI: 10.1083/jcb.200706028
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cells in culture possess primary cilia with hedgehog signaling machinery

Abstract: Human embryonic stem cells (hESCs) are potential therapeutic tools and models of human development. With a growing interest in primary cilia in signal transduction pathways that are crucial for embryological development and tissue differentiation and interest in mechanisms regulating human hESC differentiation, demonstrating the existence of primary cilia and the localization of signaling components in undifferentiated hESCs establishes a mechanistic basis for the regulation of hESC differentiation. Using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
112
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 29 publications
12
112
1
3
Order By: Relevance
“…The A1 peptide tag is specifically recognized by the AcpS enzyme. Enzymatic activity transfers a Ppant group in the CoA substrate to a serine residue in the A1 tag ( (10,(19)(20)(21)(22)(23)(24). Cilial accumulation of A1::Smo::GFP in response to ShhN treatment was confirmed by costaining with two additional primary cilium markers-anti-Arl13b ( Fig.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The A1 peptide tag is specifically recognized by the AcpS enzyme. Enzymatic activity transfers a Ppant group in the CoA substrate to a serine residue in the A1 tag ( (10,(19)(20)(21)(22)(23)(24). Cilial accumulation of A1::Smo::GFP in response to ShhN treatment was confirmed by costaining with two additional primary cilium markers-anti-Arl13b ( Fig.…”
mentioning
confidence: 86%
“…17). Multiple components of the Hh pathway localize to the primary cilium or its basal body, including Sonic Hedgehog (Shh) (10,18), Ptch1 (10), Smo (10,(19)(20)(21)(22)(23)(24), suppressor of Fused (suFU) (a key negative regulator of Gli activity), and Gli transcription factors (21,24,25). In the absence of Shh, Ptch1 is enriched in the primary cilium of cultured mammalian cells; its cilial localization is lost after engagement with Shh ligand (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the ability of both PKD and control iPS cells to elaborate primary cilia, which has been previously reported in ES cells. 29 Unstarved, undifferentiated OCT4-positive ES or iPS cells cultured on glass for 7 days in pluripotent stem cell media elaborated short primary cilia containing acetylated a-tubulin ( Figure 3C). Quantitative comparison revealed similar numbers of ciliated cells among ES, control iPS, ADPKD, and ARPKD iPS cells ( Figure 3D).…”
Section: Proliferation Apoptosis and Ciliogenesis In Pkd Ips Cellsmentioning
confidence: 99%
“…Recent research has demonstrated that cilia function as sensory units that coordinate a variety of signal transduction pathways essential for embryonic and postnatal development as well as tissue homeostasis in the adult body Eggenschwiler and Anderson, 2007;Kiprilov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%